Nimodipine attenuates dibutyl phthalate‐induced learning and memory impairment in kun ming mice: An in vivo study based on bioinformatics analysis. Issue 5 (18th December 2020) - Yan, Biao; Ma, Ping; Chen, Shaohui; Cheng, Hongguo; Tang, Min; Sun, Yanling; Yang, Xu; Wu, Yang; Cheng, Menglin
Abstract: Dibutyl phthalate (DBP), a typical representative of phthalate esters (PAEs), is used as a plasticizer in various industrial applications and has been reported to be responsible for neurobehavioral changes. Despite mounting evidence showing that nimodipine (Nim) palys a neuropharmacological and psychopharmacological role in neurons, the attenuating effects of Nim on learning and memory impairment induced by DBP exposure remain unknown. Based on bioinformatics analysis we found that the biological processes affected by both DBP and Nim may involve the calcium signaling pathway, the MAPK signaling pathway and the apoptosis pathway. The results of an in vivo study confirmed that DBP affects the levels of Ca 2+ ‐related proteins, up‐regulates phosphorylated ‐ERK1/2 expression and results in hippocampal neuronal damage and apoptosis, whereas Nim as a Ca 2+ antagonist, has a certain neuroprotective role to avoid these adverse effects. Our data suggest that Nim could be used to attenuate the learning and memory impairment in DBP‐exposed mice, to down‐regulate intracellular Ca 2+ levels, subordinate the ERK1/2 pathway and attenuate apoptosis in hippocampal tissue. Abstract :